The artist's handbook - Smith, Ray, 1949- (New York : Knopf, 1987)
A practical guide to all the tools, techniques, and materials of painting, drawing, printmaking, and related visual arts, both traditional and modern.
Includes index.
Bibliography: p. 344-345.
Booklist starred.
Young Adult
Keywords: Art -- Technique; Artists' materials; Art -- Technique; Artists' materials